Stability and beyond-use date of anesthetic agents used in surgical procedures: a review: Stability and Beyond-Use Data of Anesthesia - Wijayanti, Shofia; Hanifah, Suci; Fudholi, Dhomas Hatta (Universitas Islam Indonesia, 2024)
Background: Anaesthesia drugs are often divided into other syringes to be soluted or mixed with other medications to share with other patients for the sake of efficiency. Objectives: This study aims to know the stability of anesthetic agents and the compatibility with co-simultaneous drugs used. Methods: This review was conducted by searching literature through the following databases: PubMed, Science Direct, and Google Scholar. The keywords used in the search for articles were